(untitled) (Research, Society and Development, 2021)
The use of obturator prosthesis aims to correct the sequelae left by the surgical procedure. Its function is to separate the communication between the oral cavity and the upper areas, protecting the trauma or surgical defect, contributing to the restoration of important functions for the quality of life of the patient. chewing, swallowing and hearing, in addition to the aesthetic benefits. 12 patients were treated, coming from Hospital Dr. Luiz Antônio, who underwent an anamnesis, extra physical examination and intra oral, answered specific questionnaires Brazilian Portuguese, version 3.0 (EORTC QLQC30) and Brazilian Portuguese (EORTC QLQ-H & N35) pre and post 15 days of prosthetic installation, where all data were compared before and after using Wilcoxon tests (α = 0.05). There was a significant improvement in the quality of life of patients (p = 0.009), in problems related to speech (p = 0.0131), swallowing (p = 0.0029) and social life (p = 0.0038). There was a significant increase in the quality of life of patients, a reduction in problems related to swallowing, eating socially and problems related to speech, and most patients evolved satisfactorily, having in speech their remission of hypernasality providing an intelligible form.